Perceptual video quality metric for compression artefacts: from two‐dimensional to omnidirectional. Issue 3 (5th January 2018) - Zou, Wenjie; Yang, Fuzheng; Wan, Shuai
Abstract : In this study, the perceptual video quality (PVQ) for the vogue 360‐degree video with compression artefacts viewed on the visual reality (VR) head‐mounted display (HMD) is obtained for the first time by an elaborately designed subjective experiment. The characteristic of the PVQ of omnidirectional (360‐degree) video on the VR HMD and PC monitor is then investigated. The PVQ on the HMD is found to be linearly related to the video coding quality (VCQ) on the PC monitor. A quality evaluation model is then proposed based on the mapping formula and a new assessment parameter, where the impact of the video resolution and display device is involved. In this way, the traditional video quality assessment metrics for two‐dimensional video can be extended to assess the PVQ of the 360‐degree video viewed on the HMD. At last, the video structural similarity metric is taken as an example to predict the input of the proposed model, i.e. the VCQ of the 360‐degree video. Experimental results demonstrate that the proposed model can effectively and conveniently solve the challenge of PVQ assessment for the 360‐degree video with compression distortions on the HMD.